Data from: Prey selection of Scandinavian wolves: single large or several small? - Sand, Håkan; Eklund, Ann; Zimmermann, Barbara; Wikenros, Camilla; Wabakken, Petter (Zenodo, 2017)
Research on large predator-prey interactions are often limited to the predators' primary prey, with the potential for prey switching in systems with multiple ungulate species rarely investigated. We evaluated wolf (Canis lupus) prey selection at two different spatial scales, i.e., inter- and intra-territorial, using data from 409 ungulate wolf-kills in an expanding wolf population in Scandinavia. This expansion includes a change from a one-prey into a two-prey system with variable densities of one large-sized ungulate; moose (Alces alces) and one small-sized ungulate; roe deer (Capreolus capreolus). Among wolf territories, the proportion of roe deer in wolf kills was related to both pack size and roe deer density, but not to moose density. Pairs of wolves killed a higher proportion of roe deer than did packs, and wolves switched to kill more roe deer as their density increased above a 1:1 ratio in relation to the availability of the two species. At the intra-territorial level, wolves again responded to changes in roe deer density in their prey selection whereas we found no effect of snow depth, time during winter, or other predator-related factors on the wolves' choice to kill moose or roe deer. Moose population density was only weakly related to intra-territorial prey selection. Our results show that the functional response of wolves on moose, the species hitherto considered as the main prey, was strongly dependent on the density of a smaller, alternative, ungulate prey. The impact of wolf predation on the prey species community is therefore likely to change with the composition of the multi-prey species community along with the geographical expansion of the wolf population. Data_preyselection_PlosOne Territory: wolf territory preytype: moose=1, roe deer=2 moosedensity: density of moose per 10 km2 roedensity: roe deer density per 10 km2 daynumber: the number of days after the 1th of January timesincekill: the number of days since their last kill of moose or roe deer nutritionalstatus: the nutritional status ...